Prey preferences of notonectids towards larval mosquitoes across prey ontogeny and search area. Issue 2 (21st August 2019) - Dalal, Arpita; Cuthbert, Ross N; Dick, Jaimie TA; Gupta, Susmita
Abstract: BACKGROUND: Predatory biological control agents can be effective natural means of managing pests, vectors and invasive species. However, the strength of predator–prey interactions can be regulated through context‐dependencies that often remain unquantified. In particular, refuge effects can influence the efficacy of biological agents towards target species, and such effects are often driven by prey size and search area differences. In this study, we quantify the prey preferences of two predaceous notonectids, Anisops breddini and Anisops sardeus, towards four different aquatic larval instar stages of the medically important mosquito Culex quinquefasciatus across variations in surface area and water depth. RESULTS: Consumption rates differed significantly among the four larval sizes but not between the notonectids. Search area variations also elicited differences in consumption rates. Both predators tended to prefer second‐instar mosquito prey among surface area and water depth variations, while generally avoiding the largest (fourth instar) and smallest (first instar) prey instar stages. For both predators, differential selectivity traits were emergent across surface area variations and water depth, with refuge effects for small prey generally greatest at intermediate–large depths with high surface areas. We thus demonstrate that predatory impacts of notonectids towards mosquito larvae differ significantly according to prey size, and likely peak at intermediate size classes. CONCLUSION: Different mosquito size classes often coexist and compete, selectivity has important implications for adult mosquito proliferations. Further, in ephemeral aquatic habitats where surface areas and water depths are highly variable spatiotemporally, the efficacy of notonectids in controlling mosquito prey may differ substantially. © 2019 Society of Chemical Industry Abstract : Notonectids are important predators of mosquito larvae in an artificial habitat. Shifts in size preference were observed for four mosquito instars across three water depths and three surface areas.